PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA MEDIUM GAMBUT YANG TERGENANG SECARA PERIODIK YANG DIPUPUK DENGAN PUPUK PELENGKAP CAIR DENGAN FREKWENSI YANG BERBEDA PADA SAAT BIBIT TIDAK TERGENANG - Riki Noviantoni; Gunawan Tabrani; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the effect of giving PPC interaction with different frequencies when not flooded in the medium periodically flooded peat on the growth of seedlings of oil palm (Elaeis guineensis Jacq.). This research has been carried on in the greenhouse UPT Faculty of Agriculture, University of Riau, Pekanbaru, from November 2013 to February 2014. This study used a completely randomized factorial design consisting of two factors and three replications. The first factor is the concentration of PPC consists of 4 levels K0: no PPC, K1: 0.2%, K2: 0.4%, K3: 0.6% and the second factor spraying frequency F1 PPC Consist 3 levels: 1 times, F2: 2 times, F3: 3 times. Parameters those observed: change of plant height, increase the number of leaves, stem diameter, length of the primary root, root number, root volume, the ratio of the shoot root ratio. The data mean separation use DMRT at %. The results show that there is interaction between the concentration and frequency of PPC spraying were the parameters plant height, primary root length, shoot root ratio. A PPC concentration of 0.4% and 0.6% to add 3.17 to 3.78 of the leaves, concentrations of 0.4% and 0.6% to add 9.05 cm to 9.40 cm in diameter rod, concentrations of 0, 4% and 0.6% to add 15.22 to 16.55 strands strands, number of primary roots, a PPC concentration of 0.2% to 0.6% shows the root volume amounted to 95.22 ml to 98.88 ml. Keywords: oil palm, flooding, complementary liquid fertilizer and peat